NON-DISCRIMINATION AND RIGHT TO DIVERSITY: WHAT'S NEW FOR DISABLED PEOPLE IN THE AI ERA? (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
In the last decade, the European Union has faced profound changes due to the Covid-19 pandemic, recent military conflicts, and technological advancements such as Big Data, cloud computing, IoT, and AI systems. These developments have led to a new legal framework for citizens and businesses, encompassing old and new rights. This paper examines the condition of disability. This particular condition of vulnerability indeed serves as a litmus test for the effectiveness of the right to non-discrimination and the mechanisms protecting it. It outlines the legal definition of disability, the key regulations, and the European legal context. A discussion on equality introduces the right to diversity. The paper concludes with reflections on AI's potential to enhance disability rights, emphasizing the importance of transparent, GDPR-compliant practices and ongoing collaboration among institutions and technology providers.
Keywords: Artificial Intelligence; Disability; Nondiscrimination; Diversity; Data protection